2018
DOI: 10.2135/cropsci2018.04.0228
|View full text |Cite
|
Sign up to set email alerts
|

Maturity Traits Related to Climate Adaptation Affect Quality Characteristics in Hard Red Spring Wheat

Abstract: Maturity traits such as days to heading and days to physiological maturity have a large impact on agronomic characteristics of wheat (Triticum aestivum L.) cultivars grown in specific environments. Extended green leaf and green glume duration after heading in hard red spring wheat have been shown to result in longer grain‐fill duration, increased kernel weight, and higher grain yield in dry environments. The genetic relationship between maturity traits, seed quality, and functional bread‐making characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…This characteristic is associated with high yield in dryland environments in Montana (Naruoka et al., ). The trait is also associated with lower gluten strength (Blake et al., ). A possible reason for this is that delayed senescence results in grain filling during the hottest part of the summer.…”
Section: Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…This characteristic is associated with high yield in dryland environments in Montana (Naruoka et al., ). The trait is also associated with lower gluten strength (Blake et al., ). A possible reason for this is that delayed senescence results in grain filling during the hottest part of the summer.…”
Section: Characteristicsmentioning
confidence: 99%
“…Blake et al. () showed that a significant trend over a century of wheat breeding has been toward cultivars with extended green leaf duration after heading. ‘Vida’ (PI 642366) (Lanning et al., ) has been the most widely grown cultivar in Montana since 2011.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations